2020
DOI: 10.1002/cphc.202000113
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effect Parameters: Extending the Applications to Organometallic Chemistry

Abstract: Typically, metal complexes are constituted of an acceptor metal ion and one or more Iigands containing the donor atoms. Accordingly, the properties of a metal complex are equally dependent on the nature of the metal ion and the ligands. Minute structural variations in the ligand will may result in linear changes in the respective energetic parameters and such linear relationships have paramount importance in organometallic chemistry. The variation in ligands is virtually limitless and substantial because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Recently, the electron-rich/deficient character of lone-pair bearing nitrogen (V N ) centers in substituted 1, 10-phenanthroline (phen*) systems and their coordination ability with Mo(CO) 4 were quantified using MESP parameters. 171,172 The MESP-based substituent parameter (ΔV C ) deduced for benzene systems showed transferability property to the metal complex and it was used to predict reactivity patterns of various metal carbonyls. The electron donation from the phenanthroline ligands to the metal center led to increased negative character for MESP at CO ligands which decreased the CO stretching frequency.…”
Section: Mesp As An Electronic Parametermentioning
confidence: 99%
“…Recently, the electron-rich/deficient character of lone-pair bearing nitrogen (V N ) centers in substituted 1, 10-phenanthroline (phen*) systems and their coordination ability with Mo(CO) 4 were quantified using MESP parameters. 171,172 The MESP-based substituent parameter (ΔV C ) deduced for benzene systems showed transferability property to the metal complex and it was used to predict reactivity patterns of various metal carbonyls. The electron donation from the phenanthroline ligands to the metal center led to increased negative character for MESP at CO ligands which decreased the CO stretching frequency.…”
Section: Mesp As An Electronic Parametermentioning
confidence: 99%
“…NO is found to be strongly adsorbed on B 12 P 12 , Be 12 O 12 , Ca 12 O 12 , and C 24 , and CO is strongly adsorbed on B 12 N 12 , B 12 P 12 , Be 12 O 12 , and C 24 . The deepest molecular electrostatic potential (MESP) minimum, V min , indicates the electron-rich sites such as lone pairs and π-bonds of the molecules. An interesting finding is that the V min values of the X 12 Y 12 nanocages are linearly proportional to their CO 2 or NO adsorption energies. The insights from this work will further assist in the design and development of efficient materials for gas capture and storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Further research was conducted to establish a strong linear correlation between the Hammett (and other related) parameters and the electrostatic potentials at the critical points of substituted aromatic rings, [13][14][15][16] reaction sites, 17 or the centres of the specific atoms, including the nitrogen atoms from amine groups 16,18 or carbon atoms on aromatic rings. 19 Furthermore, it was reported that MESP can be applied to linear regression with calculated electronic properties such as Tolman electronic parameter, 20,21 the interaction energy between transition metal complex and chelate, 21 and that between cation and substituted p-conjugated ring. 22 The usage of MESP is not limited to the ground state of molecule.…”
Section: Introductionmentioning
confidence: 99%